I Stand in My Place With My Own Day Here : Site-Specific Art at The New School - Rocciolo, Silvia; Matthews, Lydia (Professor of Visual Culture); Stark, Eric (Curator); Richard, Frances (Frances M.) (Book collections on Project MUSE., 2019)
Features essays by more than fifty renowned international writers who consider thirteen monumental works of art created for The New School between 1930 and the present. The nucleus of The New School's Art Collection, these commissions--ranking among the finest site-specific works in New York City--range from murals by Jose Clemente Orozco and Thomas Hart Benton to installations by Agnes Denes, Kara Walker, Alfredo Jaar, Glenn Ligon, Sol LeWitt, and Martin Puryear + Michael Van Valkenburgh, among others. Providing a kaleidoscopic view into these works, this richly illustrated volume explores each installation through three to four essays written by critics, poets, and scholars from diverse fields including anthropology, mathematics, art history, media studies, and design. Their texts are complemented by three additional essays reflecting on each piece's art historical significance; the architectural contexts in which the works reside on the university's campus; and The New School's relationship to adventurous art practice. Also included is a roundtable discussion among leading arts educators and artists who reflect on the pedagogical potential of a campus-based contemporary art collection. The book's final section presents a history of each commissioned work, highlighted by archival images never before published.